Survival costs of within‐ and between‐season mate change in the European blackbird Turdus merula. (2nd July 2018) - Jankowiak, Łukasz; Cholewa, Marta; Wysocki, Dariusz
Abstract : Many studies of socially monogamous birds discuss the adaptive role of between‐season partner change, but only a handful of them refer to the benefits of pair fidelity in terms of increased survival. Moreover, there are no studies describing the benefits of within‐season mate retention. Our data relating to an urban population of European blackbirds Turdus merula enabled us to test the dependence of survival on pair faithfulness. Because blackbirds divorce within and between seasons, we were able to test the influence of pair faithfulness on their within‐ and between‐season survival and mate fidelity. For this purpose, we used a multievent capture–mark–recapture (MECMR) statistical model, which is based on recapture rates and different pair states (faithful to mate, paired with new partner, or dead). Our study indicated that between‐ and within‐season survival depends on pair states: pair‐bond duration increases survival to the next capture occasion in both sexes. We found that the pair‐bond duration to the current partner increased the chances of being with the same partner during the next breeding occasion, although we failed to find any within‐season pair‐bond influence for females. Our results showed sex differences in mating at the end of the season: females had a much smaller chance of breeding with the current new partner in the next year. This study has demonstrated that within‐ and between‐season survival is dependent on mate retention, and we discuss this in the context of how searching for a new partner could affect the birds' survival.